Driving organisational sustainability in the Nigerian insurance sector: The role of competitive intelligence - Joyce M. Odiachi; Owolabi Lateef Kuye; Abdul Hameed Adeola Sulaimon (SPOUDAI - Journal of Economics and Business, 2021)
Traditional insurance is being threatened as the global business environment becomes more competitive. This paper investigates the influence of competitive intelligence on organizational sustainability of the Nigerian insurance industry. The study employed a cross-sectional survey design in data collection from selected companies. Evaluation of the measurement and structural models was done using SPSS AMOS 23 to confirm reliability and validity and also test the hypotheses. The results show that individually, competitor intelligence, product intelligence and strategic intelligence all have a significant relationship with organisational sustainability. However, technological intelligence and market intelligence have no significant relationship with organisational sustainability. The results further reveal that when combined, dimensions of competitive intelligence namely technological, strategic, product, market and competitor, have a positive relationship with organisational sustainability. The study while highlighting the importance of competitive intelligence and organisational sustainability in the Nigerian insurance industry reveals concentration only on a few areas. It thus recommends that there is a need for the insurance industry to recognise and enhance the application and implementation of competitive intelligence across all facets of the organisation's operations.
Keywords: G20; J24; M19; 330; Competitive intelligence; Technological intelligence; Market intelligence; Product intelligence; Strategic intelligence; Competitor intelligence; Organisational sustainability